Management flexibility of a grassland agroecosystem: A modeling approach based on viability theory. (October 2015) - Sabatier, R.; Oates, L.G.; Jackson, R.D.
Abstract: A growing awareness of the negative consequences induced by post-WWII conventional agriculture has led to renewed interest for grazing-based livestock farming systems. A major characteristic of grassland based farming systems is the high unpredictability of forage resource in grassland ecosystems due to weather uncertainty. Two main management strategies can be followed by farmers to cope with this uncertainty: rely on ecosystem resistance — the ability of the system to remain viable for a wide range of environmental conditions or work with ecosystem flexibility by monitoring and adapting management strategies in response to perturbations. With a strategy based on resistance the farmer defines a priori the grazing sequence and does not modify it with time, while a strategy based on flexibility (also called adaptive management) requires defining grazing sequences that can be modified (adapted) in response to the environmental conditions observed. In this study we developed a simple model of a grassland agroecosystem dynamics under the mathematical framework of viability theory so as to quantify the resistance and flexibility of a set of grazing sequences. Our results show (1) for a given grazing sequence, applying a flexibility strategy leads to higher levels of production than a resistance strategy (+ 100 LU days ha − 1 on average), (2) the number of adaptations needed to maintain system viability increases with the level of production and decreases with the resistance of the system, and (3) grazing sequences requiring the most adaptations to stay viable are also the ones with the lowest potential of adaptation (flexibility). We conclude that grazing sequences are located along a gradient ranging from low production with high resistance and high flexibility, to high production with low resistance and low flexibility and requiring constant adaptations to remain viable. Adaptive management makes it possible to benefit from environmental variability and increase the level of production, while management strategies based on resistance are coherent when managers do not target maximal production and can maintain a margin to cope with unexpected events. Highlights: Graziers may adopt flexible or resistant strategies to cope with weather uncertainty. Trade-offs occur between flexibility, resistance and production. Resistant strategy (or over-capacity) is coherent for low levels of production. Flexible strategy (or adaptive management) is coherent for high levels of production.